KINERJA SISTEM FILTRASI DALAM MENURUNKAN KANDUNGAN TDS, Fe, DAN ORGANIK DALAM PENGOLAHAN AIR MINUM - Kaslum, Leila; ., Anerasari; Zikri, Ahmad; Tanjung, Yesi; Oktavia, Yaya; A, Aulia; ., Lismayani; ., Arinda (KINETIKA, 2019)
Clean water has not been able to fully the needs of the community, where there are still a number of people who use well water to fully their water needs.. Well water has high content of Fe and Mn that must give special treatment so that the quality of the water produced can meet standards. The study focused on the design of two-stage filtration equipment. The first stage of filtration uses a multi media filter with the contents of zeolite, silica sand and activated carbon. The second stage of filtration using a micro membrane filter with a pore size of 0.5,0.3 and 0.1 Î¼m. After processing the well water through device designed, the optimum treatment results are obtained at a flow rate of 33 ml / s with a reduction in TDS content of 35%, a reduction in Fe content of 76.19% and a decrease in organic matter content of 78.76%. These three parameters have met the quality standards based on PERMENKES RI No.492 / Per / IV / 2010 with TDS content of 494 mg / l, Fe of 0.01 mg / l and organic matter content of 1.2 mg / l